Batch adsorption and isothermic studies of malachite green dye adsorption using Leucaena leucocephala biomass as potential adsorbent in water treatment - Yen Chen Lee; Mohd Hazim Mohamad Amini; Nurul Syuhada Sulaiman; Mohamed Mazlan; Jia Geng Boon (2018)
The adsorption properties of Leucaena leucocephala biomass to clean malachite green contaminated water were investigated in this work. BET surface analysis showed a surface area of 0.5724 m²/g. Batch adsorption studies and isothermic studies determined that the best time and temperature for the adsorption process to become efficient were 60 min of contact time and 25 °C, respectively. The KF value of 0.3372 mg adsorbed per mg of adsorbent of the L. leucocephala biomass for malachite green was the highest at 50 °C. It was shown that the n values were n <1 which suggested that malachite green dye adsorption on L. leucocephala biomass is favorable. Values of the correlation coefficient (R2) indicated that the Freundlich isotherm can be used for the adsorption of malachite green on L. leucocephala. The results also suggest that L. leucocephala biomass can be utilized as an adsorbent for malachite green dye from wastewater at a lower cost.